System of National Accounts 2008 - United Nations (United Nations, 2010)
The System of National Accounts, 2008 (2008 SNA) is an updated version of the System of National Accounts, 1993 (1993 SNA). The 2008 SNA starts with an introduction and an overview and then presents the accounting rules, the accounts and tables, and their integration.